P‐Nitrophenol Degradation Using N‐Doped Reduced Graphene‐CdS Nanocomposites. Issue 4 (6th November 2017) - Gharedaghi, Sepideh; Kimiagar, Salimeh; Safa, Saeed
Abstract : A series of nitrogen doped reduce graphene‐CdS (NRGC) nanocomposites were successfully synthesized by using hydrothermal method. The structure and morphology of the samples were characterized by using FTIR, XRD, SEM, and PL. Photocatalytic activity of the nanocomposites for removing P‐nitrophenol (PNP) pollutant was studied under both ultra‐violet (UV) and visible light irradiation. The results show that NRGC nanocomposites exhibited higher photocatalytic activity than pure CdS. The degradation rate significantly increased to 50 and 70% by the addition of nitrogen doped reduced grapheme oxide (NRGO) to CdS under UV and visible irradiation, respectively. Higher photocatalytic activity of the nanocomposites was due to the role of NRGO as an excellent electron acceptor and transporter. Abstract : Nitrogen doped reduce graphene‐Cds (NRGC)nanocomposites are synthesized by using hydrothermal method . Photocatalytic activity of the nanocomposites for removing P‐nitrophenol pollution is studied under both ultra‐violet (UV) and visible light irradiation. The degradation rate significantly increases to 50% and 70% by the addition of NRGO to Cds under UV and visible irradiation, respectively. Photocatalytic mechanism is shown in the figure.